Active Coaxial and Active Inverted Coaxial Magnetron Electronic Guns - Meilus, J. O.; Petrauskas, Z.; Smith, M. J. A. (Elektronika ir Elektrotechnika, 2004)
It is proposed to use the principles of the coaxial and inverted coaxial magnetrons for creation of highly effective crossed – fieldactive coaxial and active inverted coaxial electron guns that not only produce, bunch and inject electron stream into next cascade of theM-type amplifier or frequency transducer, but also ensure high frequency stability, large output signal power and operation at highertemporal harmonics and subharmonics of the input signal. Both magnetron active coaxial and active coaxial inverted electron gunsshould include a high quality coaxial resonator connected with the slow – wave system operating at π-oscillations but in a first case thisresonator covers the slow –wave system and a cathode and in a second one – a large cathode with inner emitting surface covers slow –wave system and stabilizing resonator. Working duration of the devices using such active coaxial magnetron guns should be 3 – 5 timeslarger in comparison with ordinary magnetron guns because of released thermal regime of operation. The expressions for evaluation ofelektronic efficiency and ultimate increase in a gain of the active coaxial magnetron gun are presented. They confirm the high efficiencyof the gun. Ill. 5, bibl. 6 (in English; summaries in Lithuanian, English and Russian).